2017
DOI: 10.4103/0019-5413.197551
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in Pirani clubfoot severity scoring system between the orthopedic surgeons

Abstract: Background:Congenital talipes equinovarus (clubfoot) is one of the most common congenital pediatric orthopedic foot deformity, which varies in severity and clinical course. Assessment of severity of the club foot deformity is essential to assess the initial severity of deformity, to monitor the progress of treatment, to prognosticate, and to identify early relapse. Pirani's scoring system is most acceptable and popular for club foot deformity assessment because it is simple, quick, cost effective, and easy. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The Pirani and Dimeglio classifications are the two most widely utilized scoring systems for clubfoot, and their intra-observer and inter-observer reliability has been shown to be good by their developers at their respective institutions 18 , 19 . A recent study showed that even the reliability test was carried out by five different orthopaedic surgeons, except for emptiness of the heel (EH), the total score and component clinical signs of the Pirani scoring system had substantial reliability with ICCs and Kappa values of posterior crease (PC), EH, rigidity of equinus (RE), hind foot score (HFS), medial crease (MC), curvature of lateral border (CLB), lateral head of talus (LHT), midfoot score (MFS), and total score (TS) were 0.4022, 0.3255, 0.6546, 0.6221, 0.4294, 0.5322, 0.534, 0.6407, and 0.7004 and 0.46, 0.39, 0.68, 0.66, 0.43, 0.56, 0.53, 0.68, and 0.71, respectively 10 . With a three-point classification of severity of each clinical sign, the Pirani scoring system may have little room for error between assessors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pirani and Dimeglio classifications are the two most widely utilized scoring systems for clubfoot, and their intra-observer and inter-observer reliability has been shown to be good by their developers at their respective institutions 18 , 19 . A recent study showed that even the reliability test was carried out by five different orthopaedic surgeons, except for emptiness of the heel (EH), the total score and component clinical signs of the Pirani scoring system had substantial reliability with ICCs and Kappa values of posterior crease (PC), EH, rigidity of equinus (RE), hind foot score (HFS), medial crease (MC), curvature of lateral border (CLB), lateral head of talus (LHT), midfoot score (MFS), and total score (TS) were 0.4022, 0.3255, 0.6546, 0.6221, 0.4294, 0.5322, 0.534, 0.6407, and 0.7004 and 0.46, 0.39, 0.68, 0.66, 0.43, 0.56, 0.53, 0.68, and 0.71, respectively 10 . With a three-point classification of severity of each clinical sign, the Pirani scoring system may have little room for error between assessors.…”
Section: Discussionmentioning
confidence: 99%
“…The intra-class correlation coefficients (ICCs; 2-way random effects model, single-measure reliability) were calculated for initial Pirani and Dimeglio scores acquired by the two reviewers. A score of 0.81 to 1 were rated as very good, 0.61 to 0.8 as good, 0.41 to 0.6 as moderate, and less than 0.4 as poor reliability 10 . The difference in standardized deformity between the Pirani score and Dimeglio scores was calculated by paired sample t-test.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies reported that there is no universal standard assessment method available at present to quantify the initial severity of the clubfoot or monitor the clubfoot treatment (Jain et al, 2001 ; Gigante et al, 2004 ; Dyer and Davis, 2006 ; Ramanathan et al, 2009 ; Ramanathan and Abboud, 2010 ; Yapp et al, 2012 ; Bhaskar and Patni, 2013 ). Because it is difficult to obtain the objective measurements from all these classification systems (Catterrall classification system, Pirani scoring, Dimeglio classification system, and Harrold and Walker classification system) due to subjective in nature (Wainwright et al, 2002 ; Jain et al, 2012 , 2017 ; Fan et al, 2017 ). In view of imaging assessment methods, it provides objective details of severities of the clubfoot.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical grading systems had been reported with excellent reliability and reproducibility (Flynn et al, 1999 ; Pirani et al, 2008 ; Shaheen et al, 2012 ). Also, the Pirani scoring system is gained more popularity than other scoring system for assessing the outcome of Ponseti treatment (Jain et al, 2017 ). Although these both systems considered as an effective assessment tools, some aspects of prognostic measurements, such as medial and posterior creases, cavus, and heel emptiness values are considered as imperfect (Chu et al, 2010 ; Bergerault et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation